Perbandingan Kurikulum Sejarah di Indonesia dan Kurikulum Australia pada Tingkat Menegah Pertama - Rezni, Vebiana Anugrah; Yusuf, Syafruddin; Pamulaan, Alif Bahtiar (Sukma: Jurnal Pendidikan, 2024)
This research is a qualitative literature study research with a comparative method. The method used in this research uses the comparative research model from Bereday to present and analyze this research data. Testing the validity of the data was carried out by source triangulation which was carried out by analyzing various literature sources. The purpose of writing this article is to compare the history curriculum developed in Indonesia with that in Australia. The analysis focused on curriculum elements, materials and assessments from the two countries, namely Indonesia and Australia. The results of the analysis show that there are differences between the Indonesian and Australian history curricula, namely in terms of elements, materials and assessment. Indonesia emphasizes the formation of historical awareness and national identity, while Australia places more emphasis on developing interest, understanding and historical inquiry skills. The Indonesian system emphasizes concept and process skills, while Australia has material that is more integrated between knowledge and understanding and skills. On the evaluation side, Indonesia gives freedom to educational units, while Australia uses various types of tests. Although different in approach, both share a common focus on developing a deep understanding of history and analytical skills in students